Peran Politik Kyai dalam Pengendalian Konflik Pemilihan Kepala Desa (Pilkades) - Rozi, Syaikhu; Saifudin, Saifudin; Rohmad, M. Ali; Syarif, M. (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
As a reality, conflict can occur anywhere, whenever and experienced by anyone due to certain factors, one of which is the process and the results of the Election of Village Heads (PILKADES). Election of Village Head which is carried out directly to elect village leaders, in practice it is often to use money politics and